Control of Stem‐Cell Behavior by Fine Tuning the Supramolecular Assemblies of Low‐Molecular‐Weight Gelators1. Issue 15 (18th February 2015) - Latxague, Laurent; Ramin, Michael A.; Appavoo, Ananda; Berto, Pierre; Maisani, Mathieu; Ehret, Camille; Chassande, Olivier; Barthélémy, Philippe
Abstract Controlling the behavior of stem cells through the supramolecular architecture of the extracellular matrix remains an important challenge in the culture of stem cells. Herein, we report on a new generation of low‐molecular‐weight gelators (LMWG) for the culture of isolated stem cells. The bola‐amphiphile structures derived from nucleolipids feature unique rheological and biological properties suitable for tissue engineering applications. The bola‐amphiphile‐based hydrogel scaffold exhibits the following essential properties: it is nontoxic, easy to handle, injectable, and features a biocompatible rheology. The reported glycosyl‐nucleoside bola‐amphiphiles (GNBA) are the first examples of LMWG that allow the culture of isolated stem cells in a gel matrix. The results (TEM observations and rheology) suggest that the supramolecular organizations of the matrix play a role in the behavior of stem cells in 3D environments.